Pregled terapijskih opcija za liječenje spinalne mišićne atrofije: Treatments approch for SMA - Singh, Arun; Jain, Monica; Kapadia, Rupa; Kumar Mahawar, Dhirendra; Kakkar, Shivankan; Dadhich, Jaya; Chandel, Ritesh Kumar (Scripta Medica, 2021)
Spinal Muscular Atrophy (SMA) is uncommon genetic (autosomal recessive) disease that deteriorates neuromuscular function of the affected person’s body by causing lower motor neuron damage, progress in muscle atrophy and in advanced cases leads to paralysis of muscles. Mainly skeletal and respiratory muscles are involved. SMA is present due to lack of SMA proteins, which are encoded by survival motor neuron-1 (SMN-1) genes. In mutation of SMN-1 genes, deficiency of SMN proteins occurs. SMA affects all age groups, but mainly and most severely children younger than 6 months of age. At present, risdiplam is a treatment option and the drug has been approved by the US Food Drug and Administration on 7 August 2020. The availability of the drug has led to increased financial, ethical and medical problems. SMA affected populations are regularly challenged to these issues.
Keywords: Spinalna mišićna atrofija; SMN-1; Učestalost retkih bolesti; Terapija; Risdiplam; Nusinersin; Onasemnogen abeparvovek; Terapijske mogućnosti